Inhibition of Lysozyme by Taurine Dibromamine - Petronio, M. S. [UNESP]; Ximenes, Valdecir Farias [UNESP] (Bentham Science Publ Ltd, 2013)
Hypobromous acid (HOBr) is a powerful oxidant produced by stimulated neutrophils and eosinophils. Taurine, a non-protein amino acid present in high amounts in the leukocytes, reacts instantaneously with HOBr leading to their haloamine derivative taurine dibromamine (Tau-NBr2). Lysozyme is a bactericidal enzyme also present in leukocytes and in secretory fluids. The inhibition of lysozyme is a pathway for bacterial proliferation in inflammatory sites. Here, we investigated the inhibition of the enzymatic activity of lysozyme when it was submitted to oxidation by Tau-NBr2. We found that the oxidation of lysozyme by Tau-NBr2 decreased its enzymatic activity in 80%, which was significant higher compared to the effect of its precursor HOBr (30%). The study and comparison of Tau-NBr2 and HOBr regarding the alterations provoked in the intrinsic fluorescence, synchronous fluorescence, resonance light scattering and near and far-UV circular dichroism spectra of lysozyme and oxidized lysozyme revealed that tryptophan residues in the active site of the protein were the main target for Tau-NBr2 and could explain its efficacy as inhibitor of lysozyme enzymatic activity. This property of Tau-NBr2 may have pathological significance, since it can be easily produced in the inflammatory sites.
Keywords: Eosinophils; hypobromous acid; hypochlorous acid; lysozyme; neutrophils; taurine dibromamine